THE MACROECONOMIC IMPACT OF NATURAL DISASTERS IN DEVELOPING COUNTRIES: EVIDENCE FROM HURRICANE STRIKES IN THE CENTRAL AMERICAN AND CARIBBEAN REGION - Eric Strobl (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
In this paper we investigate the macroeconomic impact of natural disasters in developing countries by examining hurricane strikes in the Central American and Caribbean region. Our innovation in this regard is to employ a windfield model combined with a power dissipation equation on hurricane track data to arrive at a more scientifically based index of potential local destruction. This index allows us to identify potential damages at a detailed geographical level, compare hurricanes' destructiveness, as well as identify the countries most affected, without having to rely on potentially questionable monetary loss estimates. Combining our destruction index with macroeconomic data we show that the average hurricane strike caused output to fall by up to 0.8 percentage points in the region, although this crucially depends on controlling for local economic characteristics of the country affected.
Keywords: E0; 330; economic growth; hurricanes